Implementasi Bahasa Python Dalam Menganalisis Pengaruh Rokok Terhadap Risiko Pasien Terkena Penyakit Stroke (Universitas Sains dan Teknologi Komputer Semarang, 2023)
This study discusses the implementation of Python programming language in analyzing the influence of smoking habits on the risk of stroke in patients. The study utilizes the